Borderline papillary serous tumor of the ovary: the authors' observation and a concise review of literature - Z. N. Shavladze; T. P. Berezovskaya; A. A. Proshin; L. I. Krikunova; L. S. Mkrtchyan; N. I. Sychenkova; Yu. T. Neborak (ABV-press, 2014)
The paper presents a case of borderline papillary serous cystadenoma in a 34-year-old female patient, by describing the magnetic resonance image of borderline ovarian tumors in detail and reviewing the data available in the literature on the specific features of their imaging and diagnosis.